Physical plasma therapy accelerates wound re‐epithelialisation and enhances extracellular matrix formation in cutaneous skin grafts. Issue 4 (7th October 2020) - Frescaline, Nadira; Duchesne, Constance; Favier, Maryline; Onifarasoaniaina, Rachel; Guilbert, Thomas; Uzan, Georges; Banzet, Sébastien; Rousseau, Antoine; Lataillade, Jean‐Jacques
Abstract: Skin grafting is a surgical method of cutaneous reconstruction, which provides volumetric replacement in wounds unable to heal by primary intention. Clinically, full‐thickness skin grafts (FTSGs) are placed in aesthetically sensitive and mechanically demanding areas such as the hands, face, and neck. Complete or partial graft failure is the primary complication associated with this surgical procedure. Strategies aimed at improving the rate of skin graft integration will reduce the incidence of graft failure. Cold atmospheric plasma (CAP) is an emerging technology offering innovative clinical applications. The aim of this study was to test the therapeutic potential of CAP to improve wound healing and skin graft integration into the recipient site. In vitro models that mimic wound healing were used to investigate the ability of CAP to enhance cellular migration, a key factor in cutaneous tissue repair. We demonstrated that CAP enhanced the migration of epidermal keratinocytes and dermal fibroblasts. This increased cellular migration was possibly induced by the low dose of reactive oxygen and nitrogen species produced by CAP. Using a mouse model of burn wound reconstructed with a full‐thickness skin graft, we showed that wounds treated with CAP healed faster than did control wounds. Immunohistochemical wound analysis showed that CAP treatment enhanced the expression of the dermal–epidermal junction components, which are vital for successful skin graft integration. CAP treatment was characterised by increased levels of Tgfbr1 mRNA and collagen I protein in vivo, suggesting enhanced wound maturity and extracellular matrix deposition. Mechanistically, we show that CAP induced the activation of the canonical SMAD‐dependent TGF‐β 1 pathway in primary human dermal fibroblasts, which may explain the increased collagen I synthesis in vitro . These studies revealed that CAP improved wound repair and skin graft integration via mechanisms involving extracellular matrix formation. CAP offers a novel approach for treating cutaneous wounds and skin grafts. © 2020 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.